A new species of Umanella Gauld (Hymenoptera: Ichneumonidae: Pimplinae) from Colombia - Herrera-Florez, Andres Fabian; Molina, Oscar Efrain Ortega (Zootaxa, 2018)
A new species of Umanella Gauld 1991, U. tricoloripes Herrera-Florez, sp. n., is described from two males collected in Colombia. Umanella tricoloripes sp. nov. differs substantially from the other species of the genus in color pattern.